The essential persona lifecycle : your guide to building and using personas - Adlin, Tamara (Morgan Kaufmann Publishers, 2010)
Personas play an essential role in the development of successful products. Without creating profiles of target customers and studying them throughout your product development lifecycle, it's impossible to truly understand user need, context, and pain points. The Essential Persona Lifecycle is an easy-to-reference guide on persona creation, use, and evaluation. Whether you are a student or a UX practitioner, if you are developing products that people are intended to use, this book is for you. *Practical and immediately applicable how-to reference guide for building and u.